Astrocytes enhance the invasion potential of glioblastoma stem-like cells. - Barbara H Rath; Joshlean M Fair; Muhammad Jamal; Kevin Camphausen; Philip J Tofilon (PLoS ONE)
Glioblastomas (GBMs) are characterized as highly invasive; the contribution of GBM stem-like cells (GSCs) to the invasive phenotype, however, has not been completely defined. Towards this end, we have defined the invasion potential of CD133+ GSCs and their differentiated CD133- counterparts grown under standard in vitro conditions and in co-culture with astrocytes. Using a trans-well assay, astrocytes or astrocyte conditioned media in the bottom chamber significantly increased the invasion of GSCs yet had no effect on CD133- cells. In addition, a monolayer invasion assay showed that the GSCs invaded farther into an astrocyte monolayer than their differentiated progeny. Gene expression profiles were generated from two GSC lines grown in trans-well culture with astrocytes in the bottom chamber or directly in contact with astrocyte monolayers. In each co-culture model, genes whose expression was commonly increased in both GSC lines involved cell movement and included a number of genes that have been previously associated with tumor cell invasion. Similar gene expression modifications were not detected in CD133- cells co-cultured under the same conditions with astrocytes. Finally, evaluation of the secretome of astrocytes grown in monolayer identified a number of chemokines and cytokines associated with tumor cell invasion. These data suggest that astrocytes enhance the invasion of CD133+ GSCs and provide additional support for a critical role of brain microenvironment in the regulation of GBM biology.